Operator Idle Time Rectification as the Solution to Cycle Time Reduction in Oxygen Sensor Production - Melvin Harsono; Joni Welman Simatupang (Institute of Research and Community Outreach - Petra Christian University, 2018)
In factory works, there are systems that need to be followed in order to create a well-ordered process such that Just In Time (JIT) production can be reached. The lean manufacturing principle is one of the solutions for sustainable factory system. Within the lean manufacturing system, there are many tools that can be applied for sustainability and improvement. In this paper, Kaizen, the Japanese business philosophy as one of the lean manufacturing principle tools, is applied to give an improvement in reducing production cost. It is done by continuous observation, note, and analysis of time consumption required by the production line. A new Kaizen analysis from a new point of view is applied by comparing the impact of adding operator to the production line to the Over Time (OT) cost and renewing part of the machine-tool mapping for faster Takt Time (TT). Kaizen activity was successfully analyzed. It shows that the production Cycle Time (CT) can be deducted by 0.5 seconds which will reduce the production revenue cost by 10.8%.